Patient Health Services at Individual Practice Doctors in Muna District - Filhayah, Wa Ode; Risky, Sartini; Jayadipraja, Erwin Azizi (Magister Kesehatan Universitas Mandala Waluya, 2023)
Introduction: The phenomenon that occurs in the field shows that now many practicing doctors are opening practices like the BPJS program which opens family doctor services. In general, one district has 4,7 and 10 practicing doctors and each practicing doctor has BPJS patients. However, there is a discrepancy in the field, namely that there are still general practitioners who have many BPJS patients and some of them have few patients. In terms of science or competence and facilities, it shows that for general practitioners to have the same knowledge the reality in the field is that there are still many practicing doctors who are a few times their patients. Therefore I feel interested in finding out if it is the doctor who has the problem, the patient, or the facility. Methods: The type of research in this study is a qualitative method, which is a study aimed at describing and analyzing phenomena, events, activities, social, attitudes, beliefs, and perceptions of people individually and in groups. Result: Research results show that Based on the informant's statement, it can be seen that patients who come for treatment at the clinic of an individual practice doctor get good service and the officers are very friendly so patients do not have the desire to move to another primary facility. Conclusion: In general, health services at individual pre-training doctors (DPP) contribute greatly to improving patient satisfaction in Muna Regency.